Experimental justification for restoration of the coracoclavicular ligament in injuries of the acromioclavicular joint - Golovakha, Maksim; Zabielin, Ivan; Shishka, Igor; Banit, Oleg; Babich, Yuriy; Tverdovsky, Anatoliy; Krasnoperov, Sergiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The article presents results of an experimental and anatomical study of the acromioclavicular joint. The purpose of the work was to investigate the topographic anatomy of the joint, its ligamentous apparatus and the character of anatomical changes, depending upon the severity of injuries. The research was conducted on cadavers of both sexes. The results of the above work demonstrate that the recovery of the coracoclavicular ligament is a necessary link in the surgical treatment of dislocations in the acromial extremity of clavicle for creating a stable and functional fixation.